Metastasiertes Prostatakarzinom: Positionspapier zum Einsatz der Chemotherapie = Metastasized prostate cancer : position paper on the use of chemotherapy - Ohlmann, Carsten-Henning; Duensing, Stefan (Der Urologe, 2015)
Background Antihormonal and cytotoxic therapy options are available for the therapy of metastasized prostate cancer (mPC). Because no comparative studies are available, especially for castration-resistant prostate cancer (mCRCP), it remains unclear which patients will profit best from which therapy.Objectives Previous data on the sequence of the various therapy options show that correct selection of the first line therapy for mCRPC can have an influence on the prognosis of the patient. In this position paper the various therapy options are critically illustrated and the clinical and pathohistological criteria for selection of the first line therapy of mCRPC are discussed.Results Molecular markers are an important aid for future patient selection and individualized therapy for optimal use of the available forms of therapy.
Gesehen am 29.03.2017